Folate as an Adjuvant Therapy in Methanol Poisoning. (6th June 2019) - Theobald, Jillian; Lim, Christopher
Abstract: Folate and its derivatives have long been used as an adjunctive treatment in methanol poisoning. Methanol is ultimately metabolized to formate, the toxic compound. The accumulation of formate can lead to acidemia, retinal damage, visual impairment, and death. Formate is converted to carbon dioxide and water in a folate‐dependent manner, and folate is often given in cases of methanol poisoning. In this paper, the evidence for folate as an adjunctive therapy in methanol poisoning is reviewed.